Upaya Meningkatkan Aktivitas Dan Hasil Belajar IPS Melalui Model Pembelajaran Problem Based Learning Pada Materi Dinamika Kependudukan Indonesia Siswa Kelas VII MTsS Krueng Raya - Syamsidar, Syamsidar (Jurnal Pendidikan dan Pengabdian Vokasi (JP2V), 2020)
The purpose of this study was to improve social studies activities and learning outcomes in Indonesian population dynamics material for grade VII students of MTsS Krueng Raya in 2019/2020 Academic Year. The model used in this study is the Problem Based Learning Model. The subjects of this class ac-tion research were VII grade students of MTsS Krueng Raya in 2019/2020 school year. The number of students is 16 students with a total of 7 male students and 9 female students. This research was conduct-ed in the 2019/2020 school year within a period of 3 months, from September 2019 to November 2019 in odd semester. The methodology of this research is Classroom Action Research (CAR) which consists of two cycles and each cycle consists of two meetings. Each cycle consists of planning, implementing ac-tions and reflecting. The research procedure consisted of pre-research, planning cycle one, implementing cycle one, observing cycle one, reflection cycle one, planning cycle two, implementing cycle action two, observing cycle two and reflection cycle two. Data collection technique is to collect the value of the test carried out at the end of each learning in each cycle by using the question instrument (written test). Ob-servation data is done by marking the number of students who are active in the learning process. Data were analyzed by means of percentage statistics. The results showed that there was an increase in stu-dent learning activities in both cycles, from the category of being good enough and the good category increasing to very good. Completeness of student learning outcomes has increased from 37.50% in pre-study increased to 68.75% in the first cycle and increased to 87.50% in the second cycle. The applica-tion of the Problem Based Learning model can improve social studies activities and learning outcomes in the Indonesian population dynamics material for grade VII students of MTsS Krueng Raya in 2019/2020 Academic Year.